Ripple Effect of Abusive Supervision in the Form of Stress and Turnover Intention (KASBIT Business Journal, 2026)
This paper investigates the role of stress in the relationship between dimensions of abusive supervision and turnover intention. Three separate questionnaires were developed and distributed among the professionals of the IT Sector of Karachi in three waves. A total of 506 useable sets of questionnaires were received and included in the study. Confirmatory Factor Analysis (CFA) and three separate Structural Equation Models were used as the statistical techniques. Results indicate that dimensions of abusive supervision significantly predict stress and turnover intention. Furthermore, it is also found that stress mediates the relationship between dimensions of abusive supervision and turnover intention. Since, it is found that dimensions of abusive supervision are related to stress which in turn results in turnover intention, therefore, it is recommended that in order to reduce the stress and turnover intention of employees, managers in the IT sector should not get involved in the abuse at the workplace.